Effect of tannin levels in sorghum silage and concentrate supplementation on apparent digestibility and methane emission in beef cattle - de Oliveira, Simone Gisele; Berchielli, Telma Teresinha [UNESP]; Pedreira, Marcio dos Santos; Primavesi, Odo; Frighetto, Rosa; Lima, Magda Aparecida (Elsevier B.V., 2007)
This study evaluated the effect of diets containing sorghum silages with higher (HT) and lower-tannin (LT) concentrations supplemented with concentrate or urea on intake, digestibility, ruminal digestibility, methane emission and rumen parameters in beef cattle. Four treatments were distributed according to a 2 x 2 factorial arrangement in a duplicate 4 x 4 Latin square: LT sorghum silage + urea, LT sorghum silage + concentrate, HT sorghum silage + urea, and HT sorghum silage + concentrate. Total digestibility of the organic matter was higher when concentrate was included in the diet (0.749 and 0.753 in the LT and HT treatments, respectively). It was observed lower ruminal apparent digested matter of neutral detergent fiber in HT diets. There was no effect of tannin levels on digestibility and methane emission. The supplementation with concentrate in the LT diet decreased gas losses as a function of gross energy intake in comparison to the supplementation of the diet with urea. These results suggest the potential of concentrate supplementation to minimize energy loss as methane emission by ruminants and increase the efficiency of energy utilization. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: global greenhouse gases; nutritive value; ruminal fermentation; polyphenols